Differences in the structure of variability in ground reaction force trajectories provide additional information about variability in the golf swing - Jones, K. M.; Wallace, E. S.; Otto, S. R. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2018)
The study presents a novel application of measures of the structure of variability to ground reaction force trajectories and highlights the use of such measures to provide valuable information about coordination of the golf swing. The variability and regularity of ground reaction force trajectories were quantified for iron and driver shots from three participants with different skill levels. Pointwise median absolute deviation was used to indicate the variability of ground reaction force trajectories across their length, and two alternative methodologies, sample entropy and cross-sample entropy, were used to determine their regularity. For both driver and iron shots, results showed that while there was no difference in the magnitude of variability between any of the participants, there were differences in the structure of this variability. In general, the ground reaction force of the highest skilled participant was significantly more regular than that of the lesser skilled golfers. However, differences occurred across the various components of ground reaction force. Thus, entropy measures can provide additional valuable information concerning dissimilarities among golfers of various skill levels and may indicate differences in neuromuscular system coordination during the golf swing. This study highlights the importance of considering the structure of variability, as well as its magnitude, and describes methods which could be applied to further investigations.